2020
DOI: 10.1111/jfpe.13400
|View full text |Cite
|
Sign up to set email alerts
|

Roasting impact on the chemical and physical structure of Criollo cocoa variety (Theobroma cacao L)

Abstract: This work analyzed the effect of infrared roasting at 100, 150, and 200 C on the main physical and chemical changes of cocoa. Raw and roasted cocoa were analyzed using Brunauer-Emmett-Teller, Fourier transform infrared spectroscopy, modulated differential scanning calorimetry (MDSC), thermogravimetric analysis (TGA), SPME, and GC-MS. Using MDSC, the fusion of fat at around 35 C, and the desolvation of water and volatile compounds were identified. TGA detected loss of mass of various groups of chemical compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 85 publications
(96 reference statements)
2
17
0
2
Order By: Relevance
“…Similar to other seeds or nuts for food applications [ 45 , 47 , 82 , 83 , 84 , 85 ], roasting is a necessary heating process for enhanced use of cottonseed kernels as nutrient food products [ 23 ]. While roasting temperatures were reported in the range of 100 to 160 °C for various plant-based butters [ 86 ], the negligible CO 2 and CO bands (2400–2300 cm −1 ) in TG-FTIR spectra of Gd-k and Gl-k below 215 °C of the first shoulder in DTG curves ( Figure 5 ) suggested that the cottonseed kernels could be roasted in the temperature range without significant occurrence of decomposition (carbonization).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other seeds or nuts for food applications [ 45 , 47 , 82 , 83 , 84 , 85 ], roasting is a necessary heating process for enhanced use of cottonseed kernels as nutrient food products [ 23 ]. While roasting temperatures were reported in the range of 100 to 160 °C for various plant-based butters [ 86 ], the negligible CO 2 and CO bands (2400–2300 cm −1 ) in TG-FTIR spectra of Gd-k and Gl-k below 215 °C of the first shoulder in DTG curves ( Figure 5 ) suggested that the cottonseed kernels could be roasted in the temperature range without significant occurrence of decomposition (carbonization).…”
Section: Resultsmentioning
confidence: 99%
“…Heat treatments such as roasting and frying are frequently employed in the food processing of seeds and nuts to improve their sensory quality, digestibility, and microbiological safety [ 43 , 44 , 45 ]. Thus, TG analysis has been applied to detect the mass loss of various volatile compounds as well as appropriate roasting temperatures for heat treatments [ 44 , 46 , 47 ]. The coupling of TG with FTIR (i.e., TG-FTIR) has provided a unique capability to obtain the transient mass loss and evaluation of the volatile functional groups of a sample, which could not be obtained by the TG and FTIR individually [ 42 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos têm demonstrado que temperaturas entre 104 °C e 190 °C propiciam a perda de alguns compostos voláteis, mas também a formação de novos compostos (Diaconeasa et al, 2019;Kusçu & Bulantekin, 2016;Rojas et al, 2020). Alguns autores relatam que a perda de compostos voláteis pode ocorrer pela evaporação ou degradação durante o processo de obtenção em altas temperaturas (Bonneau et al, 2016;Oliver-Simancas et al, 2020b).…”
Section: unclassified
“…Among cocoa pure lines, Criollo is one of the varieties of high quality [ 9 ]. Thus, the aim of this work was to investigate the biological properties and the chemical composition of two different samples of Criollo var.…”
Section: Introductionmentioning
confidence: 99%